2019
DOI: 10.3892/etm.2019.7631
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR4 inhibits allergic responses in murine allergic rhinitis by regulating the NF‑κB pathway

Abstract: The present study investigated the underlying mechanisms and effects of toll-like receptor 4 (TLR4) on a mouse model of allergic rhinitis (AR). An ovalbumin (OVA)-induced mouse model of AR was treated with TLR4-short hairpin RNA (shRNA). Allergic symptoms were then subsequently assessed. Protein levels of OVA-specific immunoglobulin E (IgE), eosinophil cation protein (ECP), leukotriene C4 (LTC4) and prostaglandin D2 (PGD2) in mice serum and nasal lavage fluid, as well as various inflammatory cytokine mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Intranasal administration of lidocaine. The total amount for intranasal administration is usually 20 µl (23). During the experiment, 1, 3 and 5 mg/kg/day lidocaine was intranasally administered to mice (n=10) 3 h prior to OVA challenge on days 28-34.…”
Section: Methodsmentioning
confidence: 99%
“…Intranasal administration of lidocaine. The total amount for intranasal administration is usually 20 µl (23). During the experiment, 1, 3 and 5 mg/kg/day lidocaine was intranasally administered to mice (n=10) 3 h prior to OVA challenge on days 28-34.…”
Section: Methodsmentioning
confidence: 99%
“…Although a large body of research investigated the implication of TLRs, particularly TLR4, in allergic airway inflammation (19,(21)(22)(23)(24), only few studies focused specifically on pollen sources. The stimulation of epithelial cells by short ragweed pollen (Ambrosia artemisiifolia) was shown to result from a TLR4-dependent secretion of TSLP and IL-33, two key alarmins associated with the induction of Th2 responses and allergic sensitization (25).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously found that the mRNA and protein levels of TLR4 were significantly increased in nasal mucosa of patients with pollen-induced AR [ 13 ]. TLR4 inhibition alleviated allergic responses in mice with AR [ 14 ]. Previous results indicate that TLR4 plays a vital role in AR.…”
Section: Introductionmentioning
confidence: 99%